Single hydatid cyst of liver managed with laparoscopy – a case study - Paweł Osemek; Arkadiusz Chmieliński; Krzysztof Paśnik; Rafał Kidziński (Videosurgery and Other Miniinvasive Techniques)
Hydatid disease is not common in human populations of highly developed urban areas. However, increasing immigration,travel and international tourism have led to a recent increase in incidence. Surgery remains the method ofchoice in the management of hepatic hydatid cysts. Laparoscopic treatment of the disease has been questionable sofar, though it is feasible and safe in use. We report a case of an 18-year-old woman, successfully treated with total cystectomylocated in a favourable laparoscopic area – the border of the 3rd and 4th segment of the hepatic left lobe. Theoperation and hospitalization period were uncomplicated. Controlled follow-up laboratory and radiological testsshowed no remaining pathology or recurrence in any form. In conclusion we state that the laparoscopic techniqueprovides a feasible and efficacious option of treatment for some types of hydatid cysts located in the liver. It is a safeminiinvasive surgical approach which enables postoperative discomfort to be reduced and results in a quick recovery.